Effect of summer warming on growth, photosynthesis and water status in female and male Populus cathayana: implications for sex-specific drought and heat tolerances. (30th May 2020) - Liu, Junyan; Zhang, Rong; Xu, Xiao; Fowler, Joshua C; Miller, Tom E X; Dong, Tingfa
Abstract: Effects of climate warming on tree growth and physiology may be driven by direct thermal effects and/or by changes in soil moisture. Dioecious tree species usually show sexual spatial segregation along abiotic gradients; however, few studies have assessed the sex-specific responses to warming in dioecious trees. We investigated the sex-specific responses in growth, photosynthesis, nonstructural carbohydrate (NSC), water-use efficiency and whole-plant hydraulic conductance ( K P ) of the dioecious tree species Populus cathayana Rehd. under +4 °C elevated temperature with and without supplemental water. For both sexes, high-temperature treatments significantly decreased growth (height and biomass), photosynthetic rate ( A ), the ratio of A to dark respiration rate, stomatal conductance ( g s ), transpiration rate, NSC, leaf water potential and K P, but increased water-use efficiency (estimated from carbon isotope composition). Under warming with supplemental water, most traits of females did not change relative to ambient conditions, but traits of males decreased, resulting in greater sexual differences. Females showed a lower K P, and their g s and A responded more steeply with water-related traits than males. These results show that the effect of summer warming on growth and photosynthesis was driven mainly by soil moisture in female P. cathayana, while male performance was mainly related to temperature. Females may experience less thermal stress than males due to flexible water balance strategy via stomata regulation and water use.